Model Simulasi Peningkatan Ternak Sapi Induk Pola Gaduhan terhadap Curahan Tenaga Kerja: Studi Kasus di Kecamatan Amanuban Selatan, Propinsi Nusa Tenggara Timur - Stefanus Amalo; Budi Hartono; Hari Dwi Utami (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
Research was carried out on South Amanuban Sub District, East Nusa Tenggara. The objective of this study was at analyse labour allocation in raising beef cattle and non beef cattle farming from contract farming pattern, and to determine simulation model for cow number enhancement. Data were collected by interview method using structured questionaire. In total, 117 respondents were obtained by purposive sampling method. Data were analysed using Two Stage Least Square (2SLS) method and simulation analysis with application of SAS 9.1 program. Result showed that households’ labour allocation was 195.24 MLHE/year on beef cattle farming and 481.03 MLHE/year for non beef cattle farming. Simulation model indicated 50 % increased of cattle number resulted in improving household time devoted on beef cattle farming, production as well as profit of raising beef cattle.